Behaviour of FRP-confined coal rejects based backfill material under compression. (25th January 2021) - Zhao, Hongchao; Ren, Ting; Remennikov, Alex
Highlights: Coal rejects and cementitious grout are combined to develop a novel backfill material. FRP tubular standing support (FTSS) is developed for underground mines. Ultra-high molecular weight polyethylene (UHMWPE) FRP jacket is wrapped on GFRP tube. Both the strength and ductility of infill material in FTSS have been enhanced. FRP-confined concrete model can predict the behaviour of confined infill in FTSS. Abstract: This paper introduces a novel standing support incorporating fibre-reinforced polymer (FRP), termed FRP tubular standing support (FTSS). The exterior container of FTSS is the small rupture strain (SRS) GFRP tube wrapped with ultra-high molecular weight polyethylene (UHMWPE) FRP jacket with large rupture strain (LRS), while the infill is the coal rejects based backfill material (CBM). The CBM is made of industrial by-product (i.e. coal rejects) and high flowable cementitious grout material, leading to some environmental and economic benefits when it is used in underground mines. Test variables included the type of coal rejects (i.e. screened and unscreened), the thickness of SRS FRP tube (i.e. 1.5 mm and 3.0 mm) as well as the thickness of LRS FRP jacket (i.e. 2-ply, 3-ply and 4-ply). Test results showed that both the load carrying capacity and deformation ability of CBM in FTSS have been significantly enhanced attributed to the confinement provided by exterior FRP container. Existing stress–strain model for FRP-confined normal concrete can be used to reasonably predict the compressive behaviour of confined CBM in FTSS with large deformation ability. The ductile FTSS is suitable for underground spaces and infrastructures where the integrity of structure is the main concern.